Measuring the impact of service quality in telecommunication services of Pakistan: a conceptual framework - Rind, M. Malook; Khuhro, Mansoor A.; Ujan, Imran Anwar; Shah, Asadullah (Islamic Countries Society of Statistical Sciences (ISOSS), 2015)
The impact of the antecedents of service quality on customer satisfaction has been under debate in the academic literature since long. To ensure the customer satisfaction level, organizations require examining the level of customer expectations to servive in the compititive market environment. Increasing compitition in telecommunocation industry in Pkaitsn apeal service provider to welcome customer suuegtionrelated to sevive quality. The primary aim of this research paper is to propose a conceptual framework for investigating the influence of percieved quality, customer expectations and percieved value on the proposed research framework built thorough a thorough literature review, authors intend to adopt quantitative, clustered sampling approach for data collection. Aa structured Equation modelling (SEM) approach will be adopted to test and validate the acquired data. A clear understanding of the hypotheses of the hypothesized relationships in proposed conceptual framework would encourage telecommunication service providers to outline proper course of action to retain their customer base with optimal services. Findings of this utilization of their resources in maximizing profit, retaining customer base and achieving organizations goals.